Floquet-enhanced spin swaps - Haifeng Qiao (Nature Portfolio, 2021)
Information transfer between distant qubits suffers from spurious interactions and disorder. Here, the authors report up to an order of magnitude enhancement in the quality factor of a swap operation of eigenstates in a quantum dot chain, by using a periodic driving protocol inspired by discrete time crystals.